The editorials of two leading newspapers during the first 100 days of the Estrada Administration - Ignacio, Dawn Rosary S.; Pacit, Lucilyn; Palomar, Marte; Sonza, Hannah Grace R.
This study attempts to content analyze the editorials of the Philippine Daily Inquirer and the Philippine Star from July 1, 1998 to October 8, 1999. The purpose of this study is to describe the contents, context, and the themes of these editorials; to classify the themes of these editorials and the day's headline. This study likewise aims to know the general sentiment of the editorials over the first one hundred days of the Estrada administration and to establish, if there is, a trend between and among the editorials. This study utilized a semantic differential type of scale to gauge the sentiment of the editorials. No statistical significant difference (f-test statistic) was found between the editorials of the Philippine Daily Inquirer and the Philippine STAR. The general trend of mean scores however revealed that editorials of the Inquirer are moderately antagonistic, while the STAR's editorials are slightly supportive. The Inquirer's editorials are slightly critical, while that of the STAR's are slightly patronizing. The general theme of the editorials, both Inquirer and STAR were classified under the Politics/Governance theme. The Philippine Star publishes one (1) editorial daily, while the Philippine Daily Inquirer usually has two (2) editorials published daily.